Implications of Social Support as a Self-Control Resource - Pilcher, June J.; Bryant, Stewart A. (Frontiers in Behavioral Neuroscience, 2016)
Self-control is an intricate component of decision making and effectively managing day-to-day life. Failing to maintain adequate self-control can have negative effects on many desired goals and social experiences. As such, understanding how different facets of the human experience may affect self-control is an important undertaking. One area that is yet unclear is the possible relationships between social support and self-control. Research suggests that social support can be an effective resource in reducing stress and promoting health and well-being. Research has also indicated that stress can be a limiting factor on self-control. In contrast, few studies have focused on social support as a potential resource for self-control. The goal of this mini-review article is to explore the intersections between self-control and social support and encourage integration of these two relatively independent areas of research. This review will help provide a broader understanding of self-control resources and how we can better understand the relationships between social well-being and our ability to monitor and utilize our capacity to maintain self-control.